Unmanned Aerial Vehicle Attitude Determination Strategies: A Review - David Oppong; Joshua Ampofo; Eunice Akyereko Adjei; Anthony Agyei-Agyemang; Kwasi Kete Bofah; Mary Korkor Teye; Victoria Serwaa-Bonsu Acheamfour; God'sable Sitsofe Koku Aidam (Journal of Advanced Mechanical Sciences)
The attitude of an unmanned aerial vehicle is a very important flight parameter that needs to be known at every time during its flight. Throughout the ages, as technology has evolved, different approaches have been applied to determine this quantity. These approaches have often made use of an angular velocity source, linear acceleration information or magnetic field measurements. In this study, we present a review of these techniques, covering single- and multi-sensor approaches, deterministic and optimal strategies, as well as filter-based approaches. In the end, a method for deriving the attitude as is carried out in the present is suggested.